Fiqh Zakat In The Perspective Of Muhammad Hasbi Ash-Shiddieqy - Arifin, Jaenal (TAWAZUN: Journal of Sharia Economic Law, 2021)
Muhammad Hasbi Ash-Siddieqy studied at Al-Irsyad school (1926). Hasbi's expertise in ijtihad, he was able to introduce himself as a well-known intellectual in international world.  Related to the results of Hasbi's ijtihad, it describes: The state of Indonesian fiqh can be seen in Hasbi's ijtihad on zakat by referring to the view of Abu Hanifa which is different from the opinion of the majority of scholars - Hasbi is of the opinion that machines Production in large factories must be zakat.  This view is quite relevant with the context of a country builder that requires a lot of capital. Hasbi's opinion on zakat is left to the government for manage it.  Because, for Hasbi, zakat is the same as zakat development for the welfare of society, both non-Muslims and non-Muslims Muslim.  Therefore, the collection of zakat should also not only addressed to the Muslims, but also to the non-Muslim.  Then, the principle of zakat, which is taken on the type of property that is growing, assets that have sufficient nishab, and zakat assets.